PENINGKATAN KAPASITAS BUDAYA MELALUI LITERASI VISUAL DAN DIGITAL BAGI MASYARAKAT ADAT KENYAH DESA BUDAYA SUNGAI BAWANG, KABUPATEN KUTAI KARTANEGARA: Increasing Cultural Capacity through Visual and Digital Literacy for the Kenyah Indigenous Community in Sungai Bawang Cultural Village, Kutai Kartanegara Regency - Max, Jonathan Irene Sartika Dewi; Gunawan, Sindy Alicia; Setyowati, Ririn; Masrur; Augusta, Maximilianus Rafael Sangga; Sinurat, Yobel Rudy Kevin Romasundi; Kawulusan, Frans Rivaldo; Hamzah, Muhammad Qusairi (Program Studi Sastra Indonesia Universitas Mulawarman, 2023)
Abstract: This Community Service is carried out to support efforts to the advancement of Indonesian culture in a proportion of development that focuses on Cultural Human Resources coaching. Partners in this activity are the performing arts actors in Sungai Bawang Cultural Village, Kutai Kartanegara Regency, East Kalimantan. Literature studies and interactive discussions were carried out to find partners' needs, namely the need to use visual media in the context of protecting, developing, and utilizing culture. Coaching is carried out by providing material regarding objects of cultural advancement, strengthening visual and digital literacy, and the basics of photography. Because it is coaching in nature, what is achieved for the cultural capacity enhancement is the increasing knowledge of the participants to utilize visual media for inventory and dissemination of culture. Keywords: Culture Advancement, Dayak Kenyah, Digital Literacy, Indigenous People, Photography, Sungai Bawang, Visual Literacy Abstrak: Pengabdian kepada Masyarakat ini dilaksanakan untuk mendukung upaya pemajuan kebudayaan Indonesia dalam proporsi pengembangan yang fokus pada pembinaan Sumber Daya Manusia Kebudayaan. Mitra dalam kegiatan ini adalah para pelaku seni pertunjukan di Desa Budaya Sungai Bawang, Kabupaten Kutai Kartanegara, Kalimantan Timur. Studi pustaka dan diskusi interaktif dilakukan untuk mengetahui kebutuhan mitra yaitu perlunya penggunaan media visual dalam rangka perlindungan, pengembangan, dan pemanfaatan budaya. Pembinaan dilakukan dengan memberikan materi mengenai objek pemajuan budaya, penguatan literasi visual dan digital, serta dasar-dasar fotografi. Karena bersifat pembinaan, maka yang dicapai dalam peningkatan kapasitas budaya adalah meningkatnya pengetahuan peserta dalam memanfaatkan media visual untuk inventarisasi dan penyebarluasan budaya. Kata kunci: Dayak Kenyah, fotografi, literasi digital, literasi visual, masyarakat adat, pemajuan kebudayaan, Sungai Bawang